Is Treatment With Dithiothreitol More Effective Than Sonication for the Diagnosis of Prosthetic Joint Infection?. Issue 1 (January 2018) - Sambri, Andrea; Cadossi, Matteo; Giannini, Sandro; Pignatti, Giovanni; Marcacci, Maurilio; Neri, Maria Pia; Maso, Alessandra; Storni, Elisa; Gamberini, Simonetta; Naldi, Susanna; Torri, Arianna; Zannoli, Silvia; et al.
Abstract: Background: Prosthetic joint infection (PJI) is among the most-severe complications of a total joint arthroplasty. Identification of the causal organism is of paramount importance for successful treatment, and sonication of implants may aid in this identification. Dithiothreitol (DTT) treatment has been proposed as an alternative to sonication to improve diagnosis, reduce costs, and improve reliability of the procedure, but its efficacy remains poorly characterized. Questions/purposes: (1) Are DTT and sonication more sensitive and/or more specific than standard cultures of tissue samples for the diagnosis of PJI? (2) Which test (DTT or sonication) is more sensitive when the clinician does not suspect infection before surgery? (3) Which test (DTT or sonication) is more sensitive when the clinician suspects infection before surgery? Methods: Two hundred thirty-two patients undergoing revision of a knee or hip arthroplasty were prospectively evaluated in this randomized study. Cultures were performed on five tissue samples from each patient and on fluid obtained by prosthesis treatment in patients randomly assigned to sonication (117 patients) or DTT (115 patients). The reference standard against which cultures (on tissue samples and on fluids from sonication or DTT) were compared was the Musculoskeletal Infection Society definition of PJI. Results: Cultures on sonication and DTT fluids provided higher sensitivity (89% and 91%, respectively) than those on standard cultures of tissue samples (79%; p < 0.001). Among patients in whom infection was not suspected before surgery, the sensitivity of DTT was greater than that for sonication and cultures on tissue samples (100% versus 70% and 50%; p < 0.001). Among patients in whom infection was suspected before surgery, the sensitivity of DTT and sonication were not greater than that for standard cultures (89% and 94% versus 86%). Conclusions: In this randomized study, we found no difference in sensitivity between DTT and sonication for the detection of PJI, and both of those tests were more sensitive than standard tissue cultures. Thus, cultures of sonication or DTT fluid should be considered important additional tools to standard cultures for definition of PJI and should be considered together with other criteria, especially in settings where infection is not suspected before revision surgery. Level of Evidence Level I, diagnostic study.